Benign cystic Mesothelioma of Peritoneum: A Case Report and Review of Literature - Kumar, Vinita Jaggi; Jain, Dhruv (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Benign cystic peritoneal mesothelioma (BCPM) is an uncommon clinical condition with diverse presentations. Its abstruse pathogenesis and association with diverse intra- abdominal conditions make an explicit diagnosis arduous. Diagnostic veracity and conscientious followup are essential because, though benign nature, it recurs locally with potentials for malignant transformation. Hence a definitive diagnostic and surgical strategy needs to be formulated. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 120-122